Bank Competition and Financial Stability : Friends or Foes? - Beck, Thorsten (World Bank, Washington, DC, 2012)
Theory makes ambiguous predictions about the relationship between market structure and competitiveness of the banking system and banking sector stability. Empirical studies focusing on individual countries provide similarly ambiguous results, while cross-country studies point mostly to a positive relationship between competition and stability in the banking system. Where liberalization and unfettered competition have resulted in fragility, this has been mostly the consequence of regulatory and supervisory failures. The advantages of competition for an efficient and inclusive financial system are strong, and regulatory and supervisory policies should focus on an incentive-compatible environment for banking rather than try to fine-tune market structure or the degree of competition.